Leadership Styles, Job Satisfaction and Organizational Commitment among Academic Staff in Public Universities - Mwesigwa, Rogers; Tusiime, Immaculate; Ssekiziyivu, Bob (Journal of Management Development., 2020)
The purpose of this paper is to examine the relationship between leadership styles and Organizational commitment among academic staff in Ugandan Public Universities, mediated by Job Satisfaction. The study was cross-sectional, quantitative, and used correlation and regression to test the hypothesis. A sample of 353 academic staff was drawn from five public universities in Uganda, of which a response rate of 66 percent was obtained. Organizational commitment among academic staff in public universities in Uganda depends on the age of the academic staff, length of service, position level, leadership styles employed, and job satisfaction. Findings further show that job satisfaction partially mediates the relationship between leadership styles and organizational commitment. Only a single research methodological approach was employed; thus, future research through interviews could be undertaken to triangulate.
Keywords: Leadership styles, Job satisfaction, Organizational commitment, Public universities